Socialization of the Use of Social Media Properly and Correctly Without Violating the ITE Law for Malang City Residents - Ali, Moh.; Priyanti, Novie Ary; Habiburrahman , Novan; Puspaningsih, Eunike Sri; Lestari, Juniarti Wulan; Hariadi , Agung; Ferdinant Pakage (⁠International Journal of Asia Pacific Community Service, 2024)
Constitution number 19 of 2016 concerning Information and Electronic Transactions (hereinafter abbreviated as "ITE") in this dynamic era. This is considered important because of this sophisticated era, especially among young people (especially students) who are inseparable from technology, especially social media, which can have positive and negative impacts, so it is necessary to inform them that there are legal provisions (both civil and criminal) that can threaten them if they are not careful in using social media to convey expressions or opinions. The problems discussed are regarding students' and teachers' understanding of ITE regulations and the application of sanctions if they violate or commit ITE crimes. So that with this socialization, it is hoped that it can be a learning experience for Malang city residents to be wiser in using social media. This activity was carried out offline and was carried out for two days. The conclusion that can be drawn is that the awareness of Malang city residents regarding their knowledge of ITE regulations is still low, so this activity is considered as a new provision so that they can be more careful in accessing social media.